Les racines du hip hop au Québec - Cooke, Marylin (Télé-Québec, 2024)

La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Jumol-Julia Edéry’s Wedding in Early 20th Century Morocco - Cohen, Judith R. (Canadian Jewish Studies/Études juives canadiennes, 2022)

"[N]ou rasanble" : rassemblements hétérolingues et hétérogènes dans les chansons de Muzion - Leclerc, Catherine (Analyses, 2022)
Muzion a été parmi les tout premiers groupes de rap québécois à faire résonner une parole locale distinctive. Il le faisait dans un français mâtiné d’anglais et de créole haïtien, multipliant les registres et faisant des emprunts à encore d’autres langues. Cet article se penche sur les chansons du premier album du groupe, Mentalité moune morne, à partir de son hétérolinguisme et des questions d’appartenance que celui-ci soulève. Il examine la manière dont Muzion entrelace les langues, mais aussi les interpellations, défaisant l’association entre langue et identité. Le groupe s’adresse ainsi à la fois à une communauté immigrante locale (d’abord haïtienne, mais également pluriethnique et racisée) qu’il québécise, et à une communauté québécoise élargie qu’il pluralise. Le rap permet en outre à ses membres de faire entendre leurs voix individuelles distinctes, notamment grâce à des usages différenciés de la palette plurilingue du groupe. Ce faisant, ce sont les notions même d’appartenance et de communauté que Muzion se trouve à refaçonner, à l’encontre de toute forme d’homogénéisation, de figement ou de stéréotype.

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Lise Vachon and “Octobre au mois de mai”: Relistening to the Québécois Revolution - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

Marie-Claire Séguin: Feminism and Settler Colonialism in “Mater Maria” - Cancel-Bigay, Mario R. (Sounds that Fall Through the Cracks, and Other Silences and Acts of Love: Decoloniality and Anticolonialism in Puerto Rican Nueva Canción and Chanson Québécoise [thèse de doctorat, Université Columbia], 2021)

"If you see me walking alone on the road": Sephardic Songs of Exile, Expulsion, Memory – and Return - Cohen, Judith R. (Armenian and Jewish Experience between Expulsion and Destruction, 2021)

Entretien avec Blxck Cxsper - Danjé, Michaëla (Afrotrans. Perspectives, entretiens, poésie, fiction, 2021)
"Dans cet ouvrage collectif, la parole est donnée exclusivement à des personnes trans noires, vivant en France pour la grande majorité. Ce recueil coordonné par Michaëla Danjé, femme trans membre et co-fondatrice de Cases Rebelles, contient des essais, de la fiction, de la poésie, des interviews, etc. Ce livre est constitué d'une multiplicité de voix, de perspectives et d'expériences diverses. Différentes générations sont également représentées. AfroTrans est beau, complexe, riche de lumière, d'amour et de force! "--Goodreads.com

Gabriel Dharmoo + Followup - Dharmoo, Gabriel (Taking the Temperature: Crisis, Curating, and Musical Diversity, 2021)

Black Women Dancers, Jazz Culture, and “Show Biz”: Recentering Afro-Culture and Reclaiming Dancing Black Bodies in Montréal, 1920s–1950s - Jabouin, Emilie (Canadian Journal of History, 2021)
The documentary Show Girls, directed by Meilan Lam, makes an unprecedented contribution to the history of jazz and Black women jazz dancers in Montréal, Quebec, and to the conversation of jazz in Canada. Show Girls offers a glimpse into the lives of three Black women dancers of the 1920s–1950s. This essay asks what the lives of Black women dancers were like and how they navigated their career paths in terms of social and economic opportunities and barriers. I seek to better understand three points: (1) the gap in the study of jazz that generally excludes and/or separates dance and singing from the music; (2) the use of dance as a way to commercialize, sell, and give visual and conceptual meaning to jazz; (3) the importance of the Black body and the role of what I would define as “Afro- culture” in producing the ingenious and creative genre of jazz. My study suggests there is a dominant narrative of jazz, at least in academic literature, that celebrates one dimension of jazz as it was advertised in show business, and that bringing in additional components of jazz provides a counternarrative, but also a restorative, whole and more authentic story of jazz and its origins. More specifically, by re- exploring jazz as a whole culture that relies on music, song, and dance, this essay explores three major ideas. First, Black women dancers played a significant role in the success of jazz shows. Second, they articulated stories of self, freedom, and the identity of the New Negro through jazz culture and dance. Third, Black women’s bodies and art were later crystallized into images that further served to sell jazz as a product of show business.

Dick Montgomery et la personnification féminine afrodescendante en Amérique du Nord, 1935-1960 - Jacques, Raphaël (Histoire Engagée, 2021)

Socialisation musicale et sociabilités urbaines. Parcours de personnes immigrantes originaires d'Afrique du Nord à Montréal - Marcoux-Gendron, Caroline (L'interculturel contemporain au carrefour des disciplines, 2021)

Socialisation musicale, frontières culturelles et sociabilités urbaines. Les parcours des personnes immigrantes d'origine maghrébine à Montréal - Marcoux-Gendron, Caroline (Institut national de la recherche scientifique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.

Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

“Maple Leaf Rag” in Maple Leaf Country: Impressing Jazz upon Vera Guilaroff - Blais-Tremblay, Vanessa (Women and Music: A Journal of Gender and Culture, 2020)

Bïa Krieger versionista: Três cançoes de Chico Buarque em francês [Bïa Krieger, versionista. Trois chansons de Chico Buarque en français] - Cassiano, Raissa Conde (Université de São Paulo, 2020)

(Re)Presenting Indigenous Activism in the Nation's Capital: Signifying Resistance across Time and Place through Music in Alanis Obomsawin's Trick or Treaty? (2014) - Hoefnagels, Anna (Contemporary Musical Expressions in Canada, 2020)

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Reflets de la colonialité dans la scène des musiques nouvelles - Dharmoo, Gabriel (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2019)
Certains membres de la scène des musiques nouvelles souhaitent en décentrer ses racines eurocentriques et en critiquer ses tendances colonialistes. Avant même de discuter des stratégies qui pourraient constituer un cadre décolonisateur, il est utile d’identifier comment la colonialité se reflète dans cette scène. L’auteur, lui-même membre actif de celle-ci, partage des pistes de réflexion portant sur l’homogénéité culturelle du milieu, les questions d’accès, l’héritage de la musique classique, le concept de l’excellence européenne, la présomption d’universalité, la coexistence de statuts de légitimité et de marginalité, la relation ambigüe avec l’appropriation culturelle et les fondements de l’attribution du mérite.

Keyboard Fantasies: The Beverly Glenn-Copeland Story - Dixon, Posy (Greenwich Entertainment et Modern Films, 2019)

Bruit blanc; suivi de Les dispositifs sonores dans la poésie de Marie Uguay et de Joséphine Bacon - Henry, Cassandre (Université de Montréal, 2019)
Ce projet de recherche-création explore les avenues narratives d'une pensée de contrôle du corps par le sonore. Le travail de création réfléchira les mécanismes, les sentiments, les contraintes conscientes ou inconscientes de personnages face à l'environnement sonore urbain. Ces mécanismes, qu'ils soient intériorisés ou non par les personnages, permettront de penser le dispositif sonore, au sens de Foucault puis interprété par Agamben. Le dispositif crée, entre l'être sur lequel il agit et l'ensemble des dits et non-dits qu'il contient, un « processus de subjectivation », ou de « désubjectivation »: il se fait contrôle, s'organise en rapports de force. La partie création met en scène des personnages qui sont habités par des idéaux d'une libération du corps par la musique, que cette libération − ou son échec − soit spatiale, temporelle, sociale ou psychique. Ce travail se consacrera également à une analyse du recueil de Joséphine Bacon Un thé dans la toundra/ Nipishapui nete mushuat (2013) et du recueil L'Outre-vie (1979) de Marie Uguay. Ces autrices créent une dimension sonore et vocale évidente dans leurs poèmes, une sensibilité, voire une sursensibilité à l'ouïe − notamment par le teueikan (tambour) chez Bacon et par les « racines sonores » pour Uguay. Le son devient un vecteur qui permet de penser la subjectivité dans des possibles spatiaux et temporels simultanés que le corps paraît empêcher. R. Murray Schafer nomme « schizophonie » la séparation de la source d'émission du son par sa reproduction, par la multiplication des enregistrements. Ce rapport différé à la musique produite à distance du corps des musiciens − s'il s'agit de musique instrumentale − joue un rôle dans ce réseau de rapports de force, dans ce dispositif qui nous intéresse. Les sources sonores se sont aujourd'hui multipliées et apparaissent, par l'enregistrement, souvent déplacées et séparées de leur contexte de production original. Comment penser ces effets de décontextualisation? Le travail de création s'intéressera aux modalités et aux effets d'une voix énonciative travaillée par ces diverses représentations d'un corps qui entend, récepteur de réalités différées, d'une pensée du corps disséminé. Pour parler non pas seulement d'écoute, mais plutôt de ce que qui l'excède, de ce vers quoi tend l'écriture poétique: possibilité de l'écoute de l'autre, ou de l'écoute de ce qui est autre.

Musical Geographies and Iconic Music Legends: Mapping Céline Dion's Outstanding Contribution to Music and Global Popular Music Culture - Jucu, Ioan-Sebastian (Territorial Identity and Development, 2019)
Between music geography and iconic music legends, a strong connection has been established in terms of spatial and temporal analysis of popular music and the representation of national identities in the contemporary global cultures of popular music. The existing literature unveils a gap in the analysis of music geography and famous musicians, real global music icons identified with particular cultures. This paper argues that such music legends must be geographically studied to unveil their outstanding contribution to the world music cultures. Against such a background, a geographical approach that takes Canadian singer Céline Dion as a case studyis developed. The research aims to analyse Dion’s outstandingcontribution to global music culture in both spatial and temporal terms. Based on the music industry emergence, the paper focuses on how and why Céline Dion appeared in global music culture and examines her outstanding contribution with specific referenceto music cartographies and statistical research.National identity and related cultural issues beyond the music, lyrics, and performances are also addressed.The empirically led study is based on a multi-method approach and makes use of statistical data analysis, GIS methods, biographicalinquiry, the analysis of lyrics and visual methodologies,all suggesting that Dion’s contribution has greatly influenced the global popular music culture of the last few decades.Although the topics in question cannot be fully discussed within the limits of this paper, it highlights the importance of these issues and calls for further in-depth research to provide a new critical understanding of the intimate connections between popular music, legendary music icons and the recent perspectives in music geographies

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.

Revitalising language through music: a case study of music and culturally grounded pedagogy in two Kanien’ke:ha (Mohawk) language immersion programmes - Vallejo, Jessie M. (Ethnomusicology Forum, 2019)
Since the 1990s scholars, teachers, and policy makers have debated over the importance of culturally grounded or culture-based education (CBE) approaches in primary and secondary programmes. For Indigenous communities, CBE methods are often regarded as decolonising tools that support linguistic and sociocultural revitalisation efforts. A majority of Indigenous educational projects have prioritised teaching language above other cultural components, such as music, which has largely been overlooked as a powerful tool due to the pervasive assumption that traditional musical practices rely on the language to survive. This article explores how cultural components have a symbiotic rather than a hierarchical relationship, focusing on the interdependence between language and music. Based on ethnographic fieldwork and observations with four Indigenous language immersion teachers, I argue that music is a linchpin pedagogical tool that promotes intergenerational interactions, builds social relationships, and facilitates the daily use of language in and outside the classroom.
Keywords: Haudenosaunee; Indigenous; Iroquois; culture-based education; decolonisation; language immersion

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

L’intermédialité autochtone dans l’œuvre de Natasha Kanapé Fontaine : mémoire, oralité et territoire - Morin-Martel, Florence (Université de Montréal, 2018)
Ce mémoire explore la notion d’intermédialité autochtone au sein de l’oeuvre de Natasha Kanapé Fontaine. Les imbrications entre les médias seront notre point d’appui pour penser les questions de l’esthétique dans l’art autochtone actuel. Par le biais de la représentation d’un média dans un autre, nous aborderons ainsi la réactualisation des traditions orales telles que le conte, le mythe, le chant et le tambour au sein des productions de cette artiste. Notre parcours observera les structures intermédiales qui mettent en exergue la mémoire ainsi que les connaissances ancestrales. Les croisements entre l’identité et le territoire seront également discutés dans l’optique des représentations intermédiales. Ainsi, les phénomènes d’affirmation et de réactualisation des savoirs se déploient par l’utilisation de divers médias. De ce fait, la résistance environnementale et culturelle ainsi que la néo-oralité sous-tendent l’oeuvre de l’artiste et s’expriment à travers les territoires imaginaires et médiatiques.

Lhasa de Sela et la traversée des espaces - Proulx, Robert (Archiv für Textmusikforschung, 2018)
The singer-songwriter Lhasa de Sela (1972-2010) launched her career and produced her three records in Montreal where she arrived in 1991. Not only did she change the face of migrant song in Quebec, but she also enjoyed international success, embarking on long world tours and selling more than a million records. This analysis will focus on the songs from her second album, The Living Road, and will show that Lhasa de Sela transcended linguistic and artistic frontiers by crossing the geographical border when she made Montreal her home and creative hub.

“Come One, Come All”: Blackface Minstrelsy as a Canadian Tradition and Early Form of Popular Culture - Thompson, Cheryl (Towards an African Canadian Art History: Art, Memory, and Resistance, 2018)
Towards an African Art History: Art, Memory, and Resistance, is the first book to consoloidate the field of African Canadian Art History. In this book, Charmaine A. Nelson and her colleagues--a group of established and up-and-coming artists, scholars, and cultural critics--argue for an African Canadian Art History that can simultaneously examine the artistic contributions of black Canadian artists within their unique historical contexts, critique the colonial representation of black subjects by white artists, and contest the customary racial homogeneity of Canadian Art History. Challenging the traditional notions of artistic value, this groundbreaking book examines art, artists, and visual and material culture from the eighteenth century to the present, analyzing "high," "low," and popular art across various media, with a focus to offer a new perspective on Canadian Art History--an African Canadian Art History

Laura Niquay. Vivre et s’affirmer au féminin attikamekw - Audet, Véronique (Cahiers du CIÉRA, 2017)

D’exil et d’américanitude : un entretien avec Linda Bouchard - Bertrand, Simon (Circuit : musiques contemporaines, 2017)
Quebec composer Linda Bouchard (born 1957) is an extremely prolific composer, particularly active on the new music scene in the u.s. where she has lived for lengthy periods since 1989. She has composed a rich and diverse catalogue of works, ranging from orchestral music to more intimist instrumentations, and also using multimedia or improvisation. In this interview, the composer reflects on the question of exile and identity in light of her own experience, thus reliving her own artistic path while also addressing some still burning questions about the place of music creators in the global culture.
Keywords: composer; compositrice; exil; exile; identity; identité; parcours; society; société; trajectory

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.

Beverly Glenn-Copeland: Inspiring stories and advice from a boundary-breaking musician - Hockin, Johnny (Red Bull Music Academy, 2017)

Björk Digital : escale à Montréal - Marcotte, Nicolas-Alexandre (Circuit : musiques contemporaines, 2017)
An article from Circuit, on Érudit.

L'âme en tannage de Natasha Kanapé Fontaine : Souveraineté orale, territoriale et mémorielle - Marcoux, Gabrielle (Canadian Review of Comparative Literature / Revue Canadienne de Littérature Comparée, 2017)

Louise Beaudet. De Lotbinière à Broadway - Saint-Pierre, Marjolaine (Éditions du Septentrion, 2017)

Paroles inuites : création et transmission dans la chanson du Nunavik - Duvicq, Nelly (Recherches amérindiennes au Québec, 2016)
Among the forms of oral history, the song, within the Inuit culture, was general practice and quite versatile. Inheriting this tradition, the contemporary Inuit song has risen in popularity starting in the 1970’s and has not diminished since. Within the literary field, the lyrics to the Inuit songs demonstrate a remarkable vitality in which the author-composers explore various aesthetics, navigate languages and transmit a part of their culture. Taking into consideration the historical context, this article aims to reflect on the formal evolution of the modern Inuit song and examine the relations that are maintained through more traditional portrayals. Finally, the ultra-contemporary body of musical works in Nunavik is notable for being particularly trilingual yet reveals an upsurge of texts in Inuktitut. What significance will this have on the overall discourse?
Keywords: Inuit literature; Inuit songs; Inuktitut; Nunavik; canción inuit; chanson inuite; inuktitut; literatura inuit; littérature inuite; oralidad; orality; oralité

Rap, genre, langage et québéquicité : enjeux et tensions sociolinguistiques de l’accès aux espaces médiatiques à Montréal - Lesacher, Claire (Cahiers internationaux de sociolinguistique, 2016)

Listening to "Mes lames de tannage": Notes toward a Translation - Moyes, Lianne (Canadian Literature, 2016)

« La terre qui nous a vus grandir ». Le sujet et le monde chez Mara Tremblay, Ariane Moffatt et Salomé Leclerc - Pirie, Nathan (Université de Waterloo, 2016)
Cette étude inclut les œuvres de Mara Tremblay, Ariane Moffat et Salomé Leclerc et vise un objectif double : d’une part, il s’agit d’analyser des textes lyriques qui ont une indéniable qualité poétique et d’autre part, de réaliser une étude intermédiale alliant texte, musique et clip-vidéo afin de voir comment le sens d’un de ces éléments est infléchi, modifié ou complété par celui des autres éléments. L’hypothèse de recherche est qu’aujourd’hui, les auteurs-compositeurs-interprètes conçoivent leur art à travers trois langages esthétiques (le texte, la musique et la vidéo), faisant de la musique une expérience plurisensorielle et intermédiale. Pour faire émerger le message de ces artistes, on mobilisera les théories du care et l’écoféminisme afin d’analyser le discours portant sur le sujet et le monde. On vise à dégager les grands thèmes de ces œuvres à travers une synthèse de ces trois approches critiques. L’analyse du corpus vise à déterminer la qualité poétique des textes et la vision du monde que ces trois artistes diffusent.

Le rap comme activité (s) sociale (s) : dynamiques discursives et genre à Montréal (approche sociolinguistique) - Lesacher, Claire (Université Rennes 2, 2015)
Cette recherche propose d’interroger l’activité rap montréalaise d’un point de vue sociodiscursif et à l’aune du genre, à travers le prisme des pratiques, des représentations, des expériences et des trajectoires de rappeuses à Montréal. Inscrite dans le champ de la sociolinguistique et arrimée aux, ancrages théoriques et épistémologiques qui envisagent le genre comme un rapport social coproduit et les subjectivités en tant que traversées des rapports sociaux, mais jamais Pleinement déterminées par ces derniers, cette étude se base sur une enquête de terrain réalisée en 2011 auprès de rappeuses à Montréal. Axée sur un corpus discursif et interprété selon une méthode qui croise analyse du discours et analyse de contenu thématique, elle engage une approche des phénomènes et des processus à l’œuvre en tant qu’ils sont territorialisés.Les pratiques, les expériences et les représentations des rappeuses seront envisagées dans un contexte marqué par leur « rareté ». Il sera constaté qu’outre une actualisation des rapports sociaux de sexe, les pratiques et les expériences des rappeuses sont aussi impactées par les enjeux sociolinguistiques de l’espace montréalais, ainsi que par ce qui relève du concept de québéquicité. Ainsi, les rappeuses composent leurs pratiques et leurs trajectoires en étant toujours situées à une place unique, dynamique et forcément ambivalente au sein de la matrice de la domination, et qui se façonne notamment par l’imbrication du genre, du langage, des représentations sur le rap, et des héritages d’une idéologie de la francophonie canadienne-française, que réactualise notamment le concept de québéquicité contemporain.

Java to Jazz: Eva Gauthier - Spiller, Henry (Javaphilia: American Love Affairs with Javanese Music and Dance, 2015)

Rap, langues, « québéquicité » et rapports sociaux de sexe : pratiques et expériences de rappeuses montréalaises d’origine haïtienne - Lesacher, Claire (Diversité urbaine, 2014)
In the stories recounting the early days of the rap scene in Montreal, actors of Haitian descent were particularly active on the rap scene: this is evident in rap texts, where frequent occurrences of Haitian Creole can be found. Considering this characteristic of Montreal rap, we propose a reflection on the issues around the visibility of Haitian migrants, and descendants of Haitian migrants, in Quebec public space by focusing on the practices and experiences of Montreal female rappers of Haitian descent. In this contribution, which aims at understanding the processes of hegemonization and minoritization at work in the Montreal and Quebec context, we will examine in particular how the vectors of differentiation involving language, “québéquicité” or gender, are manifested and reproduced in the media coverage of artistic productions.
Keywords: Haitian community; Rap; communauté haïtienne; gender; genre; languages; langues; « québéquicité »; “québéquicité”

Native Classical: Musical Modernities, Indigenous Research Methodologies and a Kanienkéha (Mohawk) Concept of Non:wa (Now) - Witzleben, John Lawrence (Université du Maryland, 2014)
In this dissertation I explore how Indigenous methodologies that foreground cultural advocacy, revitalization, and education can be articulated using Indigenous language and cultural metaphor in research on North American Indian composers. Toward this end, I apply the Kanienkéha (Mohawk) concept of "non:wa" or "now" that also refers to three modes of perception--the now of the past, the present, and the future--toward understanding the intersection of innovation and tradition in classical Native music. This research joins the existing discourse that critiques binary oppositions separating Indigenous tradition (as past) and innovation (as present and future). Through interviews, fieldwork, and musical analysis, I illustrate Native values of interconnectedness, relationality, continuity, politics, and soundscapes in the processes of Native composition as well as the resultant works, I explore how these, in turn, may be understood through the application of Indigenous research techniques. In collaboration with a cohort of contemporary musicians, I look primarily at two Navajo composers--Raven Chacon and Juantio Becenti--and examine my own work as a composer, performer, and ethnomusicologist of Kanienkéha descent to explore the following questions: How can the topic of classical Native music best be served by using Indigenous methodologies in fieldwork, research, and representation and What is classical Native Music and is it different from other contemporary classical music styles? Drawing on the teachings of Indigenous dotahs (elders/teachers), the scholarship of ethnomusicologists, and examining oral and written tradition while using language and cosmology as cultural metaphors, I present a variety of possibilities for looking at Indigenous music through Indigenous eyes. Rather than offering a set of conclusions, I offer a set of tools for discussion and reflection: 1) how we might understand a definition of classical Native music; 2) how we are part

Enjeux culturels et sociaux de la circulation de la chanson J’attendrai dans les années 1940 - Beaudet, Simon-Pierre; Savoie, Chantal (Mens. Revue d'histoire intellectuelle et culturelle, 2013)
Cette analyse aborde le cas singulier de la circulation de la chanson J’attendrai dans la culture des années 1940, dont l’analyse des variantes permet de cerner les rapports mouvants d’une chanson aux genres chansonniers et musicaux, aux goûts et aux pratiques du public, ainsi qu’à leur ancrage au sein des champs culturels nationaux. Elle permet même, parfois, de sonder les modalités de l’évolution des modèles des rapports sociaux entre les sexes présents dans différentes versions. Ce sont ainsi autant les enjeux artistiques, culturels, sociaux et intimes à l’oeuvre qui guident notre analyse de ce cas de transfert culturel, que le repérage de vecteurs permettant de formuler une équation de la circulation culturelle des chansons à succès. , This article deals with the singular case of the circulation of the song J’attendrai in the 1940s. The analysis of the different versions of the song allows us to reveal the changing relationship between these versions and musical genres, the tastes and practices of the public, and the way they fit into national cultures. This analysis also allows us, in places, to explore the evolution of social relationships between genders as presented in the different versions of the song. This way, our analysis of this case of cultural transfer is guided as much by the artistic, cultural, social and intimate aspects of the song, as by a search for the vectors explaining the cultural circulation of a successful song.
Keywords: chanson; féministe; musicologie

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

« Donner le temps » : entretien avec Lorraine Vaillancourt - Goldman, Jonathan (Circuit : musiques contemporaines, 2013)
In an interview with Lorraine Vaillancourt, the founder and artistic director of the Nouvel Ensemble Moderne (nem) recounts her musical education in Quebec, Montreal and Paris, and goes on to describe the establishment and development of her ensemble, the choice of repertoire and her plans for the future.
Keywords: Lorraine Vaillancourt; Nouvel Ensemble Moderne; contemporary music ensemble; direction musicale; ensemble de musique contemporaine; musical conducting

Auditeurs en exil : le cas des Chiliens à Montréal et leur rapport à deux chansons emblématiques - Gonzalez, Laura Francisca Jordán (Volume !. La revue des musiques populaires, 2013)
Cet article examine l’expérience des auditeurs chiliens exilés à Montréal, se concentrant spécifiquement sur leurs écoutes pendant la dictature militaire (1973-1989). Issus d’une méthodologie mixte qui combine l’histoire orale et l’analyse musicale, les résultats de cette recherche musicologique révèlent la place primordiale que l’audition musicale eut chez les exilés dans la reconstruction d’un lien avec leur pays d’origine, ainsi que dans le développement du mouvement de solidarité avec le peuple chilien. L’article explique, d’abord, le déploiement des goûts musicaux et identifie les répertoires canoniques qui demeurent au centre des écoutes. Ensuite, il aborde le rôle de l’usage des enregistrements en vinyle et cassette, et de la radio dans la diffusion des musiques. Enfin, les deux dernières sections explorent les significations associées aux pièces musicales ‘Gracias a la Vida’ et ‘Vuelvo’, mettant en relief la complexité de la réception en ce qui concerne la construction des identités culturelles, le récit des histoires personnelles et communautaires.
Keywords: bootleg / piratage / contrefaçon; cassette / bande magnétique; communautés / minorités; migration / diaspora / exil; réception; écoute / auditeur

„A Moncton“ von Marie-Jo Thério. Chiac in Literatur und Alltag [« À Moncton » de Marie-Jo Thério. Le chiac dans la littérature et la vie quotidienne] - Reinsberg, Franziska (Grin Verlag, 2013)
„C'est boring à soir“ - Vielfältiger und vermischter zeigt sich eine Sprache nur selten. Doch was ist das, was dort zu lesen ist? Das Ziel dieser Arbeit ist die Untersuchung der sprachlichen Strukturen dieser besonderen hybriden Sprachvarietät - dem Chiac, eine Varietät des akadischen Französisch, das im Osten Kanadas gesprochen wird.

Innu nikamu - L’Innu chante. Pouvoir des chants, identité et guérison chez les Innus - Audet, Véronique (Presses de l'Université Laval, 2012)
Le présent ouvrage porte sur l’expression musicale populaire contemporaine des Innus du Québec et du Labrador (Canada). Les chants et musiques innus sont abordés dans une perspective d’affirmation identitaire et de guérison sociale liées aux processus de décolonisation et de revalorisation de la culture. L’ouvrage concerne plus précisément les Innus des communautés de Uashat mak Mani-utenam et d’Ekuanitshit situées sur la côte nord du golfe du Saint-Laurent. La création et la diffusion de chansons populaires en langue innu-aimun sont devenues depuis peu un phénomène très important dans la plupart des communautés innues. Ces chansons s’inspirent à la fois des modes traditionnels de relation au son et au monde, de la tradition de chants chrétiens en langue innu-aimun ainsi que des musiques de violoneux, country, folk, rock et des divers courants actuels. Malgré ces multiples influences, elles révèlent une attitude musicale propre aux Innus, en continuité avec un mode d’être ancestral, où le chant confère du pouvoir sur soi-même et dans le monde environnant. Ancrées dans l’expérience contemporaine, ces musiques sont des agents de transformation qui prennent aussi part au processus de guérison de l’être innu.

The Vocal Music of Ana Sokolović: Love Songs for the Twenty-First Century - Bernstein, Tamara (Circuit, 2012)
Enchanted by the vocal music of Serbian-born Canadian composer Ana Sokolović, Tamara Bernstein visited the composer at her home in Montreal. Sokolović’s music draws on several sources, including the theatrical world and the culture of the Balkans. The extended vocal techniques in Sokolović’s music are rooted not in the avant-garde music of the twentieth century, but in the oral traditions and poetic voice of Serbia. It seems that the more the composer returns to her cultural roots, the more she embraces the universality of the human soul.

El cancionero judeoespañol en transición: Un estudio de dos compilaciones de mujeres sefarditas del siglo XX [Le répertoire de chansons judéo-espagnoles en transition : étude de deux compilations de femmes sépharades du XXe siècle] - Havassy, Rivka (Ladinar, 2012)

Quand le rap dit la ville : perceptions sociolinguistiques des rappeuses de Montréal - Lesacher, Claire (Dynamiques sociolangagières de l’espace algérois. Discours et représentations, 2012)

Polyrhythmic Dance Currents: Race Multiculturalism and the Montreal Dance Community - Templeton, Melissa (Université de Californie à Riverside, 2012)

Wendat Song and Carnival Noise in the Jesuit Relations - Bloechl, Olivia (Native Acts: Indian Performance, 1603–1832, 2011)

Selanikli Humour in Montreal: the Repertoire of Bouena Sarfatty Garfinkle (1916-1977) - Cohen, Judith R. (Judeo Espaniol: Textos satíricos judeoespañoles: de salonicenses o sobre salonicenses/Satirical Texts in Judeo-Spanish by and about the Jews of Thessaloniki, 2011)

National Affection: Céline Dion - Hurley, Erin (National Performance: Representing Quebec from Expo 67 to Celine Dion, 2011)
In National Performance, Erin Hurley examines the complex relationship between performance and national identity. How do theatrical performances represent the nation in which they were created? How is Quebecois performance used to define Quebec as a nation and to cultivate a sense of 'Quebec-ness' for audiences both within and outside the province? In exploring Expo 67, the critical response to Michel Tremblay's Les Belles Soeurs, Carbone 14's image-theatre, Marco Micone's writing practices, Cľine Dion's popular music, and feminist performance of the 1970s and 80s, Hurley reveals the ways in which certain performances come to be understood as 'national' while others are relegated to sub-national or outsider status. Each chapter focuses on a particular historical moment in Quebec's modern history and a genre of performance emblematic of the moment, and uses these to elaborate the nature of the national performances. Winner of the Northeast Modern Language Association's Book Prize, National Performance is sophisticated yet accessible, seeking to enlarge the parameters of what counts as 'Quebecois' performance, while providing a thorough introduction to changing discourses of nation-ness in Quebec

La musique des Chiliens exilés à Montréal pendant la dictature (1973-1989) : la création de musiques de la résistance politique et la réception des auditeurs dans l’exil - Jordan Gonzalez, Laura Francisca (Université de Montréal, 2011)
Cette étude musicologique aborde la musique pratiquée et écoutée par les Chiliens exilés à Montréal pendant la dictature (1973-1989), se concentrant sur l’histoire de la musique du point de vue des auditeurs. Quelles musiques participent à l’expérience d’exil et quel rôle accomplissent-elles? Comment les musiques accompagnent-elles le processus d’adaptation au pays d’accueil et comment aident-elles à construire un lien avec le pays d’origine? Ce sont quelques unes des questions qui ont guidé le développement de la recherche, dont la méthodologie est mixte et se concentre sur l’entrevue. Trois dimensions de l’histoire musicale y sont examinées. Premièrement, la contribution de la pratique musicale au mouvement de solidarité envers le peuple du Chili, notamment à travers la formation d’ensembles musicaux et l’organisation des peñas et des concerts. Deuxièmement, le rôle des musiques dans la construction d’une communauté culturelle chilienne, où différents discours sur l’identité nationale et politique sont négociés. Troisièmement, la présence des musiques dans les expériences individuelles d’exil, de déracinement et d’adaptation. Les genres de musique populaire les plus présents, soit la Nueva Canción Chilena et la Proyección Folclórica, ainsi que leurs enjeux des significations identitaires et politiques, font partie de la problématique du présent texte. La cueca, considérée la danse nationale, occupe aussi une place privilégiée de la discussion, due à la place importante qu'elle occupe dans la communauté chilienne de Montréal.

Kanadisches Französisch im Unterricht - Lynda Lemay: Les maudits Français [Le français canadien en classe - Lynda Lemay : « Les maudits Français »] - Thiele, Sylvia (Varietäten im Französischunterricht. 1. Französische Fachdidaktiktagung [Les variétés dans l'enseignement du français. 1er colloque de didactique du français], 2011)

Violet Archer: A Canadian woman in composition - Banfield, Emma (Université Northwestern, 2010)

"Si mosós no las vamos a recoger...": The Songbooks of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Los sefardíes ante los retos del mundo contemporáneo. Identidad y mentalidades [Les sépharades face aux défis du monde contemporain. Identité et mentalités], 2010)

Jeunesse, musique et rituels chez les Atikamekw (Haute-Mauricie, Québec) : ethnographie d'un processus d'affirmations identitaire et culturelle en milieu autochtone - Jérôme, Laurent (Université Laval, 2010)

Interpreting success and failure: the eclectic careers of Eva and Juliette Gauthier - Slominska, Anita (Université McGill, 2009)
My dissertation explores the eclectic singing careers of sisters Eva and Juliette Gauthier. Born in Ottawa, Eva and Juliettte were aided in their musical aspirations by the patronage of Prime Minister Wilfred Laurier and his wife Lady Zoë. They both received classical vocal training in Europe. Eva spent four years in Java. She studied the local music, which later became incorporated into her concert repertoire in North America. She went on to become a leading interpreter of modern art song. Juliette became a performer of Canadian folk music in Canada, the United States and Europe, aiming to reproduce folk music “realistically” in a concert setting. My dissertation is the result of examining archival materials pertaining to their careers, combined with research into the various social and cultural worlds they traversed. Eva and Juliette’s careers are revealing of a period of transition in the arts and in social experience more generally. These transitions are related to the exploitation of non-Western people, uses of the “folk,” and the emergence of a cultural marketplace that was defined by a mixture of highbrow institutions and mass culture industries. My methodology draws from the sociology of art and cultural history, transposing Eva and Juliette Gauthier against the backdrop of the social, cultural and economic conditions that shaped their career trajectories and made them possible.

Tunes That Bind: Paul J. Seelig, Eva Gauthier, Charles T. Griffes, and the Javanese Other - Spiller, Henry (Journal of the Society for American Music, 2009)
The powerful concept of orientalism has undergone considerable refinement since Edward Said popularized the term with his eponymous book in 1978. Orientalism typically is presented as a totalizing process that creates polar oppositions between a dominating West and a subordinate East. U.S. orientalisms, however, reflect uniquely North American approaches to identity formation that include assimilating characteristics usually associated with the Other. This article explores the complex relationship among three individuals—U.S. composer Charles T. Griffes, Canadian singer Eva Gauthier, and German-trained Dutch East Indies composer Paul J. Seelig—and how they exploited the same Javanese songs to lend legitimacy to their individual artistic projects. A comparison of Griffes's and Seelig's settings of a West Javanese tune (“Kinanti”) provides an especially clear example of how contrasting approaches manifest different orientalisms. Whereas Griffes accompanied the melody with stock orientalist gestures to express his own fascination with the exotic, Seelig used chromatic harmonies and a chorale-like texture to ground the melody in the familiar, translating rather than representing its Otherness. The tunes that bind Griffes, Gauthier, and Seelig are only the raw materials from which they created their own unique orientalisms, each with its own sense of self and its own Javanese others.

"Eskimo chicks and word warriors": the creative cultural spaces of Elisapie Isaac and Taqralik Partridge - Foot, Johanna Maria (Université Carleton, 2008)

L'identité culturelle dans « Montréal », d'Ariane Moffatt : une analyse musicale sémiologique - Laurier-Cromp, Mélanie (Université McGill, 2008)
La chanson « Montréal », d'Ariane Moffatt, a remporté un vif succès durant l'été 2006. Ce mémoire examine les causes de cette popularité. Après une revue des diverses méthodes existantes en recherche en musique populaire, trois types d'analyse se succèdent. En premier lieu, l'étude présentée ici décrit la chanson de manière théorique; on y observe le fonctionnement de la voix, de la mélodie, de la métrique, de la basse, des phrases, de la tonalité, des accords et des instruments utilises, images par une transcription précise de l'enregistrement de la chanson. Puis, le présent travail étudie les codes musicaux qui se retrouvent dans «Montréal». Dans cette deuxième section, le message musical du morceau est analysé, en tenant compte du contexte socioculturel de l'été 2006, de l'histoire nationale et musicale qui a précédé la sortie de cette pièce et des paroles de la chanson. Finalement, cette étude investigue la composante identitaire de «Montréal» en examinant les croyances nationalistes des Québécois, la place de la chanson dans l'imaginaire collectif de ce peuple, et la tradition musicale populaire de la province.

L'émergence des chanteurs immigrants sur la scène de la musique populaire au Québec : l'exemple de Corneille et de Lynda Thalie - Proulx, Robert (Quebec Studies, 2008)
A l'instar des ecrivains de la litterature migrante, des chanteurs et des chanteuses venus de divers pays ont fait du Quebec leur port d'attache et le foyer de leur carriere artistique. Ce phenomene assez recent a fait qu'au cours des dix dernieres annees on a vu debarquer au Quebec des artistes d'Hai'ti, du Bresil, du Mexique, du Maroc, du Rwanda, du Tchad, de l'Algerie, et du Venezuela, chacun avec sa musique, sa couleur, et sa sensibilite propre. Dans cette nouvelle branche de la chanson quebecoise on trouve les themes de predilection de la litterature migrante tels que l'exil, la nostalgie, le sentiment de perte, l'adaptation a un nouveau pays, l'integration, le racisme, la xenophobie, et l'hospitalite. La chanson quebecoise s'enrichit de ces differents apports; car ces artistes apportent avec eux non seulement des voix, des sons et des styles musicaux nouveaux, mais aussi des themes inedits et des trames narratives originales qui refletent leur culture d'origine, leur passe, et leurs valeurs de meme que leurs emotions liees a leurs defis actueis et a leurs reves pour l'avenir. (1) Dans cet article, nous examinerons en detail l'ceuvre de deux d'entre eux: Lynda Thalie qui, selon Monique Giroux, l'experte en chanson francophone de Radio-Canada, "est, parmi les artistes neo-quebecois, celle qui a pris le plus de place et est la plus susceptible de conquerir un large public" (cite par Vignaux) et Corneille, celui qui a jusqu'a ce jour remporte le plus grand succes aussi bien commercial que d'estime. II a vendu plus d'un million et demi de ses deux premiers disques, et a lance son premier disque en anglais, "The Birth of Cornelius," au Japon en mai 2007. (2) Lynda Thalie: l'exilee d'Algerie

Three Canadian Sephardic Women and their Transplanted Repertories: From Salonica, Larache and Sarajevo to Montreal and Kahanawá:ke - Cohen, Judith R. (Folk Music, Traditional Music, Ethnomusicology: Canadian Perspectives Past and Present, 2007)

The Ladino Song in the 20th Century: A Study of the Collections of Emily Sene and Bouena Sarfatty-Garfinkle - Havassy, Rivka (Université Bar-Ilan, 2007)
Keywords: Pas de lien web

La rencontre des musiques du Moyen-Orient et de l'Occident : esthétisme, composition et analyse - Makdissi-Warren, Katia (Université de Montréal, 2007)
The object of this dissertation is the meeting of Middle-Eastern and Western music. The dissertation includes an essay and seven original compositions (scores and recordings). The text begins with the exposition of the basics of Middle-Eastern music required to understand my artistic approach. The 'taqasim', a major musical form in the Middle-East and a source of inspiration for my work is presented in more detail. The second chapter deals with the philosophy of aesthetics involved in the intermixing of musical cultures. Concerns about the coherence of commingled languages are exposed. The concepts of intermixing, cultural identity and coherence of a work are submitted for discussion. For a given work, does the notion of coherence retain its essence from one person to the next according to culture and social context? This questioning is directly linked to the creation and generation of the processes of development for the musical material in my compositions. Throughout the chapter, I position my approach in relation to the thinking of authors such as Adorno, but also relative to personal experiences. In chapter 3 I describe the writing processes I have developped in order to create a sound fabric wherein Middle-Eastern music meets that of the West. My work defines processes for treating parameters in order to draw together elements of both Eastern and Western musical expressions into a distinctive language <f> <fr><nu>.</nu><de>7</de></fr></f> the key to this is grasping how one musical element influences another. Using analysis as a starting point for the comparison of musical parameters in each of the languages, I have elaborated new commingling (intermixing) techniques. This chapter is therefore devoted to the cross-relational writing techniques that have been evolved to adequately support my artistic approach. The final chapters of this dissertation feature the detailed analyses of three of my compositions: 'Jet Stream, Algorythme and PLB'. Each piece's form, sections and sub-sections are presented followed by the analysis of its basic musical material and development.

Récit d’une Beauceronne en Irlande ou la découverte de ‘l’irlandicité’ des Québécois - Matte, Isabelle (Cap-aux-Diamants, 2007)

A Queer Protocol of Homage: Chambres de Ténèbres/Tombeau de Claude Vivier By Marko Nikodijević - Novak, Jelena (International Journal of Music New Sound, 2007)
The music of Canadian composer Claude Vivier (1948-1983) was used as a fractalized material for the creation of the composition Chambres de ténèbres/tombeau de Claude Vivier (2005) by Marko Nikodijević. Vivier’s opus and his marginal queer acting were the pillars of Nikodijević’s meticulous reading/deconstructing of Vivier’s world through his own artistic dilemmas.

Jeanne Maubourg (1875-1953) : l’apprentissage de la modernité théâtrale - Robert, Lucie (Jeu. Revue de théâtre, 2007)
Un article de la revue Jeu, diffusée par la plateforme Érudit.

Erika Mann et Pauline Julien : voix parallèles dans l'exil et l'engagement - Augustin, Myriam (Université McGill, 2006)

The Memoirs of a Partisan from Salonika - Melammed, Renee Levine (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2004)

Oralité et culture vocale inuit - Le Goff, Philippe (Revue DEMéter, 2003)

Native American Contemporary Music: The Women - Diamond, Beverley (The World of Music, 2002)
This article explores issues raised in interviews with traditional and contemporary Native American musicians and recording artists of the 1990s. It exemplifies how they view their roles vis à vis traditional gender structures and community obligations, how they draw upon different media to communicate their messages, and how they use their work as a form of social action. Their narratives reveal a wide variety of strategies by which they negotiate the double consciousness and multiple relationships of their lives, balancing historically rooted values and traditions with modern ones. I attempt to develop a feminist interpretation that is respectful of the cultural values these women expressed in their conversations with me.

Global Pop On The Move: The Fame of Céline Dion Within, Outside and Across Québec - Grenier, Line (Journal of Australian Canadian Studies, 2002)

Popularité, identité et internationalisation : les phénomènes Plamondon et Dion - Oberhuber, Andrea; Poulin, Richard (Les frontières improbables de la chanson, 2001)

Céline Dion, national unity and the English-language press in Canada - Young, David (Media, Culture & Society, 2001)
The national unity crisis in Canada deepened during the 1990s; it became increasingly likely that the French-speaking province of Quebec might separate from the rest of the country. This article examines how press coverage of Céline Dion, the popular francophone singer from Quebec, has intersected with the national unity debate. After providing some background on the debate and Dion, the article explores the linkages between them in Canada's English-language press. The analysis suggests the existence of a pro-unity frame in coverage of Dion. It also identifies how news stories about Dion have been shaped by binary oppositions, quoting practices and other journalistic techniques. The article concludes by noting some similarities and differences between coverage of political events in the national unity debate (such as referendums or constitutional accords) and coverage of Dion which is associated with the debate.
Keywords: Canadian; Québécois; anglophone; francophone; music; newspapers; politics

Questions de renommée : les mises en mémoire du phénomène Céline Dion - Grenier, Line (Recherches féministes, 2000)
Dans cet article, l'auteure se penche sur le « phénomène Céline Dion » au Québec sous l'angle de la renommée. Au moyen de quelques fragments du discours qui a alimenté ce phénomène à la fin de la dernière décennie, l'auteure esquisse les contours de deux des figures concurrentes de la renommée que ce phénomène met en évidence : le « héros national » et l'« entrepreneur heureux ». Son analyse illustre comment ces figures de la renommée et les mises en mémoire auxquelles elles prêtent visibilité et valeur, lorsqu'elles sont en action dans la conjoncture québécoise contemporaine, opèrent une fusion, sinon une collusion entre la réussite individuelle et collective, entre l'intérêt personnel et national, et, par le fait même, rattachent différents ordres de matériel culturel au présent « passé » de certaines expériences privées, ressources locales et trajectoires publiques.

L’énigme de la correspondance d’Albani à Heugel - Langlois, Maryse (Les Cahiers de la Société québécoise de recherche en musique, 2000)

La carrière d’Emma Albani au Covent Garden de Londres - Vachon, Pierre (Les Cahiers de la Société québécoise de recherche en musique, 2000)